Design of above-room-temperature ferroelectric two-dimensional layered halide perovskites. Issue 16 (7th April 2022) - Siwach, Puneet; Sikarwar, Poonam; Halpati, Jigar Shaileshkumar; Chandiran, Aravind Kumar
Abstract : This review provides design strategies for developing above-room temperature 2D halide perovskite ferroelectrics. The role of polarization in optoelectronics has been reviewed, and a roadmap for developing high-efficiency devices has been proposed. Abstract : Oxide ferroelectric materials based on the ABO3 structure possess net electric polarization at zero applied fields that give rise to new photovoltaic concepts. One of the peculiar properties specific to ferroelectric materials is the 'anomalous photovoltaic effect' (APVE), where the photovoltage of the single junction device exceeds the bandgap. Like many next-generation photovoltaic concepts, namely hot-electron harvesting, multi-exciton generation, and up- or down-conversion, the ferroelectric photovoltaics can lead to a phenomenal revolution in the solar cell domain. Although APVE is observed in oxides, these materials possess a large optical bandgap and low charge carrier diffusion length, limiting their ability for further exploration in high performance solar cells. Recently, a new class of organic–inorganic halide perovskite (OIHP) materials with exceptional structural tunability and extraordinary optoelectronic properties has emerged. These materials were successfully employed in solar cells, and have shown excellent power conversion efficiency of over 25%. A sub-class of OIHPs based on a two-dimensional layered structure was shown to possess a non-centrosymmetric structure with net ferroelectric polarization. These materials provide a new opportunity to explore the anomalous photovoltaic effect and potentially improve the conversion efficiency. There are at least 28 different layered halide perovskites with 23 unique organic cations reported to possess above-room-temperature ferroelectrics. In this review, we have analyzed all of these systems and presented three different design strategies to introduce polarization in the perovskite crystal structure: (i) alloying of organic cations that possess a net dipole, (ii) halogen substitution in organic linkers, and (iii) the use of homochiral polar molecules. In the second half of this review, we discuss the application space made possible by these ferroelectric semiconductors, namely photodetectors, solar cells, light-emitting diodes, and piezoelectric detectors. We conclude this review with a roadmap for employing these 2D-layered halide perovskite ferroelectric materials for highly efficient optoelectronic devices, specifically solar cells.